Are three colonies of Neostromboceros albicomus, a candidate biological control agent for Lygodium microphyllum, the same host biotype?. Issue 3 (3rd March 2016) - Madeira, Paul T.; Facey, Jordan; Pratt, Paul D.; Maul, Dora P.; Wheeler, Gregory
ABSTRACT: Three colonies of Neostromboceros albicomus, a candidate biological control agent of Lygodium microphyllum, were barcoded using the D2 expansion domain, to determine which of two biotypes they represented. The first colony, collected in 2005 and 2007, was used for the initial host range testing. Colonies collected in 2012 and 2014 are currently being used to finalise this testing. All three colonies were collected in Trat Province, Thailand and all three populations show identical sequences to the N. albicomus biotype which prefers L. microphyllum as its host plant. The N. albicomus biotype that uses L. flexuosum as its host plant differs by a single nucleotide, a difference which may reflect cryptic speciation.